2015
DOI: 10.1016/j.nbd.2014.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic regulation of KCC2 activity by the zinc receptor mZnR/GPR39 during seizures

Abstract: The aim of this study was to investigate the role of the synaptic metabotropic zinc receptor mZnR/GPR39 in physiological adaptation to epileptic seizures. We previously demonstrated that synaptic activation of mZnR/GPR39 enhances inhibitory drive in the hippocampus by upregulating neuronal K+/Cl− co-transporter 2 (KCC2) activity. Here, we first show that mZnR/GPR39 knockout (KO) adult mice have dramatically enhanced susceptibility to seizures triggered by a single intraperitoneal injection of kainic acid, when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 89 publications
1
84
0
Order By: Relevance
“…2012; Gilad et al . 2015). In the CA3 region, the mossy fibre (MF) terminals form specialized synapses onto CA3 pyramidal neurons.…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 99%
“…2012; Gilad et al . 2015). In the CA3 region, the mossy fibre (MF) terminals form specialized synapses onto CA3 pyramidal neurons.…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 99%
“…We first asked whether endogenous Zn 2+ levels were similar in WT and ZnR/GPR39 KO mice. Tissue samples from the distal colon were loaded with Zinpyr-1 [5355] and fluorescent signals were monitored in the presence or absence (control) of the high-affinity cell permeable Zn 2+ chelator, TPEN (20 µM). The Zn 2+ -dependent fluorescence levels were similar in control tissues from WT or ZnR/GPR39 KO, and application of TPEN significantly attenuated the fluorescent signal, indicating that the signal is triggered by Zn 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…6A – B), suggesting that Zn 2+ levels in colonocytes are similar in WT and ZnR/GPR39 KO mice. Using a similar approach it was previously shown that levels of neuronal vesicular Zn 2+ were not different in WT and ZnR/GPR39 KO tissue [55]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…extracellular versus intracellular – might result in opposite consequences. Gilad et al (2015) investigate the role of zinc (Zn 2+ ) signaling in epileptic seizures induced by the excitotoxin kainic acid and unravel an adaptive mechanism enhancing the crucial inhibitory K + /Cl − cotransporter 2 (KCC2) through the synaptic metabotropic Zn 2+ receptor mZnR/GPR39. The authors propose that synaptic Zn 2+ released from glutamatergic terminals triggers the adaptive mechanism and might therefore exert a crucial neuroprotective function to restore inhibitory drive, preventing excitotoxicity during sustained seizures.…”
mentioning
confidence: 99%